Effect of location in transverse plane for 45-degree V-baffle on flow and heat transfer mechanisms in a square channel - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2018)
Numerical predictions on flow and heat transfer in a square channel heat exchanger placed with V-baffle are examined. The gap spacing between the V-baffle and channel wall is varied for all baffle heights. The laminar regime with Re = 100 - 1000 is considered. The numerical model for the square channel heat exchanger placed with V-baffle is validated. The preliminary result reveals that the computational domain has reliability to predict flow and heat transfer in the channel. The mechanisms on flow and heat transfer in the heat exchanger channel are illustrated at the numerical result section. The thermal performance analysis of the heating section when inserted with the V-baffle is also reported in forms of the Nusselt number ratio (Nu/Nu0 or NuR), friction factor ratio (f/f0 or fR) and thermal enhancement factor (TEF). As the results, it is found the gap spacing has extremely effect for flow structure and heat transfer behavior in the test section. The optimum gap spacing ratio may help to reduce the pressure loss or improves the heat transfer rate in the channel heat exchanger. The selection for the gap spacing ratio in the heating section at various baffle heights is also concluded. In addition, the gap spacing ratio around 5 - 10% is suggested for the range investigation.
Keywords: Gap spacing; Heat exchanger; Heat transfer; Thermal performance; V-baffle